Pengaruh Model Pembelajaran Student Facilitator and Explaining Terhadap Hasil Belajar Siswa Kelas X IPS - Nandar Setya Nugraha; Maskun Maskun; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2018)
The purpose of this study was to determine the positive effect of using the Student Facilitator And Explaining model on students' cognitive learning outcomes in the Historical X Social Sciences class in Pringsewu 2 Public High School. The method used in this study is an experimental method with Posttest Only Control Design. Samples were chosen randomly using random sampling. The data analysis technique in this study is Quantitative by testing the data analysis with the T-Test test formula. Based on data analysis performed using the T-Test test. obtained the results of testing the hypothesis that t count 11.23 t table 1.67, so H0 is rejected and H1 is accepted. The results of the quantitative data analysis using Student Facilitator And Explaining learning models have a positive effect on students' cognitive learning outcomes in the history subjects of X IPS class at SMA Negeri 2 2016/2017 Academic Year.Tujuan penelitian ini untuk mengetahui pengaruh yang positif penggunaan model Student Facilitator And Explaining terhadap hasil belajar kognitif siswa pada mata pelajaran Sejarah Kelas X IPS di SMA Negeri 2 Pringsewu. Metode yang digunakan dalam penelitian ini adalah metode eksperimen dengan Posttest Only Control Design. Sampel dipilih secara Random menggunakan jenis random Sampling. Teknik analisis data dalam penelitian ini adalah Kuantitatif dengan dilakukan uji analisis data dengan rumus uji T-Test. Berdasarkan analisis data dilakukan menggunakan uji T-Test. diperoleh hasil uji hipotesis bahwa thitung 11,23 ttabel 1,67, sehingga H0 ditolak dan H1 diterima. Hasil analisis data secara kuantitatif penggunaan model pembelajaran Student Facilitator And Explaining berpengaruh positif terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah Kelas X IPS di SMA Negeri 2 Tahun Ajaran 2016/2017.Kata kunci: hasil belajar, model pembelajaran student facilitator and explaining, pengaruh